2012
DOI: 10.1038/nature11347
|View full text |Cite
|
Sign up to set email alerts
|

Division and subtraction by distinct cortical inhibitory networks in vivo

Abstract: Brain circuits process information through specialized neuronal subclasses interacting within a network. Revealing their interplay requires activating specific cells while monitoring others in a functioning circuit. Here we use a new platform for two-way light-based circuit interrogation in visual cortex in vivo to show the computational implications of modulating different subclasses of inhibitory neurons during sensory processing. We find that soma-targeting, parvalbumin-expressing (PV) neurons principally d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

44
570
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 506 publications
(617 citation statements)
references
References 45 publications
44
570
3
Order By: Relevance
“…Another optogenetic study found that activating PV inhibitory interneurons sharpened the orientation tuning and direction selectivity of the nearby pyramidal cells to which they were directly connected (Lee, et al, 2012b). In contrast to the findings of Wilson et al (2012), the sharpening was specifically due to PV interneurons because activating SOM and VIP inhibitory interneurons had no such effect. Lee, et al (2012b) showed the relevance of these effects to perceptual discrimination as measured psychophysically by activating PV interneurons in awake mice.…”
Section: Modulation That Suppresses Responses To Rf Inputmentioning
confidence: 58%
See 2 more Smart Citations
“…Another optogenetic study found that activating PV inhibitory interneurons sharpened the orientation tuning and direction selectivity of the nearby pyramidal cells to which they were directly connected (Lee, et al, 2012b). In contrast to the findings of Wilson et al (2012), the sharpening was specifically due to PV interneurons because activating SOM and VIP inhibitory interneurons had no such effect. Lee, et al (2012b) showed the relevance of these effects to perceptual discrimination as measured psychophysically by activating PV interneurons in awake mice.…”
Section: Modulation That Suppresses Responses To Rf Inputmentioning
confidence: 58%
“…Selectively reducing their activity reduced surround suppression in Layer 2/3 pyramidal neurons by between 10 and 30% . Furthermore, in accord with their putative role in surround suppression, SOM inhibitory interneurons target dendrites on nearby pyramidal cells with a wide range of orientation specificities (Wilson et al 2012). SOM interneurons are but one of several mechanisms for surround suppression, however, which is also in part inherited from earlier stages of visual processing.…”
Section: Modulation That Suppresses Responses To Rf Inputmentioning
confidence: 99%
See 1 more Smart Citation
“…Although one study showed that PV but not SOM activation enhanced stimulus selectivity 22 , another reported that SOM activation sharpened but PV activation preserved selectivity 23 . Although this difference may be due to differences in the protocols of optogenetic activation as well as basic differences in the visual stimuli themselves 22,23,47,48 , our present results demonstrated that both PV and SOM interneurons contribute to response sparseness during natural stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the expression of calcium-binding proteins and neuropeptides, interneurons can be classified into distinct groups 14,16,18,19 , among which parvalbumin (PV)-and somatostatin (SOM)-expressing neurons constitute a large fraction 14,19 . Recent studies have used optogenetic techniques to examine how the activities of PV and SOM interneurons influence properties such as cortical response gain, stimulus selectivity and spatial integration [20][21][22][23][24][25] . However, the effect of specific type of inhibitory interneuron on cortical response reliability remains uncharacterized.…”
mentioning
confidence: 99%